Calcium Sets the Clock in Ameloblasts - Said, Raed; Lobanova, Liubov; Papagerakis, Silvana; Papagerakis, Petros (Frontiers in Physiology, 2020)
Background: Stromal interaction molecule 1 (STIM1) is one of the main components of the store operated Ca2+ entry (SOCE) signaling pathway. Individuals with mutated STIM1 present severely hypomineralized enamel characterized as amelogenesis imperfecta (AI) but the downstream molecular mechanisms involved remain unclear. Circadian clock signaling plays a key role in regulating the enamel thickness and mineralization, but the effects of STIM1-mediated AI on circadian clock are unknown. Objectives: The aim of this study is to examine the potential links between SOCE and the circadian clock during amelogenesis. Methods: We have generated mice with ameloblast-specific deletion of Stim1 (Stim1fl/fl/Amelx-iCre+/+, Stim1 cKO) and analyzed circadian gene expression profile in Stim1 cKO compared to control (Stim1fl/fl/Amelx-iCre-/-) using ameloblast micro-dissection and RNA micro-array of 84 circadian genes. Expression level changes were validated by qRT-PCR and immunohistochemistry. Results: Stim1 deletion has resulted in significant up-regulation of the core circadian activator gene Brain and Muscle Aryl Hydrocarbon Receptor Nuclear Translocation 1 (Bmal1) and down-regulation of the circadian inhibitor Period 2 (Per2). Our analyses also revealed that SOCE disruption results in dysregulation of two additional circadian regulators; p38α mitogen-activated protein kinase (MAPK14) and transforming growth factor-beta1 (TGF-β1). Both MAPK14 and TGF-β1 pathways are known to play major roles in enamel secretion and their dysregulation has been previously implicated in the development of AI phenotype. Conclusions: These data indicate that disruption of SOCE significantly affects the ameloblasts molecular circadian clock, suggesting that alteration of the circadian clock may be partly involved in the development of STIM1-mediated AI.